Analysis of the Use of a Combination of Soil Embankment and Lightweight Material (Foam Mortar) as an Alternative to Slab on Pile Construction Case Study: Rengat-Pekanbaru Toll Road Construction Project Section Lingkar Pekanbaru-Junction Pekanbaru Sta 19 - Dewatama, Wahyu Maya; Mochtar, Noor Noor Endah; Mochtar, Indrasurya B.; Muliawan, Mahar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The soil condition on the Rengat - Pekanbaru Toll Road Sta 193+ 025 - Sta 193+400 which passes through oil palm plantations, swamp areas, and the Siak River, consists of a compressible layer as thick as 7.0 meters. To handle the problem, a 375 m long slab on pile construction was planned with a construction time of 3 months. However, the design was costly; therefore, alternative planning using ordinary piles and a combination of ordinary and lightweight piles was required. The rate of settlement at the study site did not meet the requirements for t = 1 year (< 2cm/year) or t = 10 years (< 10cm/10 years). Therefore, it is necessary to install PVDs with an installation distance of 1.0 meter and a length of 7.0 m. The stability analysis showed that as the percentage of foam mortar increases, the SF value increases. The bearing capacity of the subgrade was increased by installing geotextiles; the number of geotextile layers required at each site varied depending on the height of the embankment and the combination of soil + foam mortar, the thicker the foam mortar, the less geotextile layers were required. The number of reinforcing piles was also planned according to the thickness of the soil and foam mortar variations; the thicker the foam mortar, the less piles were required. In terms of cost, the slab on pile replacement structures that provide savings are geotextile-reinforced soil backfill and a combination of soil backfill with 25% thick foam mortar. Each of these replacement structures provides savings of Rp 40 billion (without foam mortar) and Rp 12.1 billion (with 25% thick foam mortar). For the implementation time, both methods require the same completion time as slab on pile which is 3.5 months.